Reliability of teledentistry mobile photos versus conventional clinical examination for dental caries diagnosis on occlusal surfaces in a group of school children: a diagnostic accuracy study - Lobna Sakr; Hala Abbas; Nahwand Thabet; Fatma Abdelgawad (BMC Oral Health)
Abstract Background Teledentistry offers an effective, cost-efficient solution for caries detection in school children, improving access to early diagnosis and preventive care in underserved areas. Through remote imaging, it enables timely assessments without in-person visits, helping bridge healthcare gaps and enhance children's oral health outcomes. Participants and methods Three examiners participated in this study, examiner 1 (E1) clinically examined the children then examined the clinical photos, examiner 2 (E2) examined the photos only, and examiner 3 (E3) took the clinical photos at school without participating in clinical examination. Sample size consisted of 141 school-going children from primary one to primary six grades. They were examined clinically by E1 using deft/DMFT indices, then clinical photos were taken for both arches from occlusal view. Occlusal surface photos were only included in the analysis. These photos were examined by E1 and E2 after a 48-h wash-out period and the same indices were measured and calibrated. Results There was a strong agreement between clinical and photo diagnosis for E1 (kw = 0.899, p < 0.001), clinical and photo diagnosis for E2 (kw = 0.834, p < 0.001), and image diagnoses (E1) and (E2) (kw = 0.898, p < 0.001). The internal consistency between clinical and photo diagnoses (E2) was acceptable 0.790 (0.706:0.85). For other scores, the internal consistency between all variables was excellent (α > 0.9). Conclusion Teledentistry provides accurate and reliable results. It is a valuable tool for school-screening programs without dental radiographs. Trial registration It was retrospectively registered on clinical trial.gov on 25/10/2024 with an identifier NCT06661837.